Sex-specific asymmetry in lumbar paraspinal muscles among chronic low back pain patients: correlation with pain duration and intensity - Sihai Liu; Luis Becker; Bernhard Hoehl; Sandra Reitmaier; Lukas Mödl; Daishui Yang; Tianwei Zhang; Matthias Pumberger; Hendrik Schmidt (Scientific Reports)
Abstract Chronic low back pain (cLBP) is a multifactorial condition, including paraspinal muscle asymmetry. Understanding the relationship between muscle asymmetry and cLBP and how this varies by sex is crucial for targeted interventions. From January 2022 to December 2023, 250 participants were enrolled: 117 without back pain (no-BP) (61 females, 56 males) and 133 with cLBP (69 females, 64 males). MRI assessed the cross-sectional area (CSA), functional CSA (FCSA), and fat infiltration (FI) of the paraspinal muscles, including the psoas major (PM), quadratus lumborum (QL), erector spinae (ES), and multifidus (MF), at all lumbar levels. Asymmetry indices were calculated for CSA (CAI), FCSA (FCAI), and FI (FIAI). Data were analyzed using multiple linear and logistic regression. Muscle asymmetries were observed in both sexes and groups, with significant differences in the CSA and FCSA of the QL in males and notable FI asymmetries in the cLBP group. In women with cLBP, higher ES CAI and FCAI at L5/S1 (p < 0.05) and lower PM FCAI at L4/5 (OR 0.869, 95% CI 1.008–1.150, p = 0.03) were observed. FIAI was significantly higher in cLBP for ES at L2/3 and PM, MF, and ES at L4/5 (p < 0.05). Men with cLBP had lower PM CAI and FCAI at L1/2 and L4/5 (p < 0.05), with varying FIAI levels. FIAI correlated with cLBP duration and intensity in both sexes (p < 0.05). Paraspinal muscle asymmetry, particularly in fat infiltration, is associated with cLBP and varies by sex. These findings support sex-specific approaches to managing cLBP.